(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This research paper focuses on the artistic and aesthetic qualities of fibre art and its design. The aim is to explore and understand the definition of fibre art, its history, materials and techniques used, vocabularies, and the designers who offer a strong background to understand how the manner of weaving, material selection, and the formation of two- and three-dimensional artefacts can work together to solve the problems of interior spatial design. It begins with analysing the functional and aesthetic elements of fibre. This portrays and explain the various techniques of fibre art as well as applied practical and technical studies of the aesthetic properties of materials we’re using. It then continues to consider the problem of artists and designers by focusing on all the principles and elements that are required in creating art forms of fibre art & design. This research study began, as all research should, with a lot of self-interest, curiosity and a desire to better understand all of the practical possibilities for the use of fibre art in our daily lives. It started when, as a practising interior designer, I became overly fascinated with the surface character of my medium that is fibre. All the interior designers are well familiar with the aesthetic properties of their textile materials and of the forms that they create using this medium i.e. fibre art. Amazing as it is, however, the practice of hand tuft crafts of fibre art itself – is also very confusing. At least it was to me, as I began to study it more firmly and objectively about fibres, their sources for extraction, the creation of fibre crafts, and, lastly, the utilitarian approach to use fibre art in our daily lives.